Evaluation of estrous cycle after transplantation of vitrified ovarian tissue in mice - Taghi Taktaz-Hafshejani; Farigol Janghorbani; Maryam Akhavan Taheri (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Vaginal cytology is an effective method for assessing the activity of the hypothalamus-pituitary-ovary axis in rodents. This study aimed to investigate the restoration of ovarian function following the transplantation of vitrified ovarian tissue by examining daily vaginal smears. Methods: In this experimental study, 20 adult female NMRI mice (8 weeks old) with regular estrous cycles were randomly divided into four groups: a control group, an ovariectomy group, a vitrified ovarian transplant (VT) group, and a non-vitrified ovarian transplant (FT) group. All groups, except the control group, underwent ovariectomy. In the VT group, the right ovary was auto-transplanted into the muscle of the same mouse after vitrification and thawing. In the FT group, the right ovary was auto-transplanted into the muscle of the same mouse without vitrification. From the fourth day after transplantation until the end of the second estrous cycle, daily vaginal smears were collected. The onset of the first proestrus in each mouse indicated the beginning of the estrous cycle, and the interval between two consecutive proestrus phases was considered a complete cycle. Results: All transplants in both the VT and FT groups were completely successful. The mean onset of the first and second estrous cycles in the VT group was significantly delayed compared to the FT and control groups (P<0.05). Although the length of the estrous cycle in the VT group increased compared to the other groups, this increase was not statistically significant. Conclusion: The findings suggest that the estrous cycle returns after vitrification and transplantation of ovarian tissue in mice. Initially, this cycle may be prolonged but tends to improve over time. Therefore, daily monitoring of the estrous cycle can effectively demonstrate the repair and restoration of function in transplanted ovarian tissue without necessitating its removal from the mice.